The Efficiency of Terpenes Extracts of Eucalyptus Camaldulensis Seed to control Larval Stage of Callosobruchus maculates (Coleoptera:Bruchidae) (Baghdad Science Journal, 2025)
The current study has beenconduced to evaluate the effect of extracted crude terpens at the concentrations of 6,8% of seeds of Eucalyptuscamaldulensison the 4th larval instar oftheCallosobruchusmaculates and the percentage of the cowpea seed germination.The Results showed that the terpens extract of the concentration of 8% increases the mortality rate of the fourth larval instar and it reach to 63.3%, and then decrease of to 26.6,20% at concentration of 6%and forcontrol treatment respectively The percentage of adult emergence reduces to 0% at the concentration of 8% compared with control treatment in which it reach to 66.6%. The extraction atbothconcentrations 6,8% does not affect the germination rate